THE DETERMINANT OF DIGITAL BASED BRAND LOYALTY WITH BRAND LOVE AS MODERATING VARIABLE OF EL’S COFFEE - Ketut Sardoni; Faurani Santi Singagerda; Nia Lefiani (Prosiding International conference on Information Technology and Business (ICITB), 2019)
The purpose of this study was to determine the effect of Brand Image, Customer Satisfaction, Brand Trust on Brand Loyalty with Brand Love as a moderating variable in El coffee in Bandar Lampung. Problems that take the study of this tends to the development of a brand that is highly influential for the growth of a business to create consumer loyalty so there is no decline. The type of research is using research quantitatively with methods of causal research. The samples in the study are totaled 100 responded by using the formula slovin and using techniques sampling purposive sampling. Research is using the method of analysis of SEM by using application Smart PLS. The hypothesis in the study to determine whether the brand image impact positively on Customer Satisfaction and Brand Trust, Are Customer Satisfaction impact positively on Brand Trust, Are Customer Satisfaction and Brand Trust impact positively on Brand Loyalty, and Customer Satisfaction, Brand Trust and Brand Loyalty influential positive to Brand Love.Keywords: Brand Image, Customer Satisfaction, Brand Trust, Brand Love, and Brand Loyalty.